Paradox of Social Capital in the Implementation of Public Policy (Finding in the Tanimbar Islands Regency) - Nikolaus Powell Reressy; Agus Pramusinto; Subando Agus Margono; Ely Susanto (Policy & Governance Review, 2019)
The era of decentralization (autonomization) has begun in Indonesia since 1999. Various public policies have been made to support the implementation of decentralization. Of the many public policies, there are those that have been successfully implemented, but not a few have experienced ineffectiveness to failure. Many studies reveal that social capital is one of the factors that supports the successful implementation of various public policies. However, there is still very little research that looks at the dark side (paradox) of social capital, which contributes to the ineffectiveness of the implementation of a public policy. This paper discusses the paradox of social capital that causes the ineffectiveness of the process of implementing a public policy. The various cases discussed in this paper show that local government as implementing institution face serious obstacles in implementing various public policies, when public policies collide with the values of social capital that are lived and trusted by the local community. The Tanimbar Islands are a small and poor regency in Maluku Province, which also experiences this problematic situation. This situation occurs when the applied public policies clash with reality regarding some forms (manifestations) of social capital found in the community, such as the cultural values of duan lolat, sweri practices, and communal lifestyles in tnyafar. By showing the case of the Tanimbar Islands, we can see the dark side of social capital in the implementation of public policies, which in the future, need to be resolved.